Analysis Of PSAK No. 109 On Financial Reporting Of Accounting For Zakat, Infaq And Sadaqah - Sari, Septia Maya; Siregar, Lukman Hakim; Susilawaty, Tengku Eka (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study aims to analyze the compliance of the financial reporting practices for zakat, infaq, and sedekah at the North Sumatra Independent Zakat Institution with the Financial Accounting Standards Statement (PSAK) No. 109. PSAK No. 109 serves as the primary guideline for the preparation of financial reports by zakat institutions to ensure transparency, accountability, and governance in accordance with sharia principles. This study employs a qualitative descriptive approach, using data collection methods such as documentation, literature review, and direct interviews. The findings indicate that the North Sumatra Independent Zakat Institution has prepared financial documents, including statements of changes in funds, statements of financial position, cash flow statements, and reports on managed assets. However, there are still shortcomings in the presentation and disclosure of information that do not fully comply with the provisions of PSAK No. 109, such as the incomplete preparation of notes to the financial statements.Therefore, improvements are needed in the recording and reporting systems to align with applicable standards and to enhance the trust of the muzakki.